Synthesis and characterization of fly ash-based geopolymer membrane for methylene blue dye removal - Ahmad Daud, N.A. (IOP Publishing Ltd, 2021)
Utilization of fly ash-based geopolymer membranes for the removal of environmentally hazardous materials has become an attractive route due to its cheaper processing cost and prolonged use. This paper reports the preparation of geopolymer composite membranes and the filtration performance of the prepared geopolymer membranes for the removal of methylene blue (MB) contaminant. The geopolymer membrane was prepared by the dissolution of raw material, i.e., fly ash in alkaline activator i.e., sodium hydroxide solution. Various proportions of foaming agents as a mixture of hydrogen peroxide and egg white were added to investigate their impacts on the prepared membrane pore structures and morphology. The morphology, pore structure and functional groups of geopolymeric composite membranes were characterized using field-emission scanning electron microscopy (FESEM), Brunauer-Emmett-Teller (BET) analysis and Fourier Transform Infrared spectroscopy (FTIR) respectively. The performance of the membranes was evaluated for the removal of MB in aqueous solution using a lab-scale membrane filtration setup. The performance tests revealed a promising result with all the rejection was above R>90 for membranes GE0, GE1, GE2.5 and GE5, meanwhile the best permeation obtained was 15 L/m2.h when GE5 was used. The results were correlated to BET and FESEM results which showed that the pore structures of GE5 were homogeneous and uniform while having the highest pore size which is 19.60 nm. Â© 2021 Institute of Physics Publishing. All rights reserved.